Efficacy of neck-specific exercises with and without internet-based support on psychological factors in chronic whiplash-associated disorders: secondary analyses of a randomized controlled trial. - Zetterberg, Hedvig; Boersma, Katja; Peolsson, Anneli; Peterson, Gunnel (Pain Medicine, 2026)
Objective Chronic whiplash-associated disorders (WAD) can involve complex interactions between physical symptoms and psychological factors, and long-term effects of exercise programs are of interest. This study aimed to evaluate the effects of a predominantly internet-based neck-specific exercise program (NSEIT) compared with the same neck-specific exercises (NSE) performed at a physiotherapy clinic on psychological outcomes in chronic WAD, including cognitive-behavioral factors (pain catastrophizing, fear-avoidance beliefs, self-efficacy), emotional distress (symptoms of depression, anxiety), and cognitive functioning. A further objective was to assess whether psychological factors moderated treatment effects on the primary outcome, neck-specific disability. Methods This secondary analysis was based on a randomized multicenter trial. Participants (n  = 140) were randomized to NSEIT or NSE. Outcomes were assessed at baseline, 3 months, and 15 months. Psychological outcomes were analyzed with mixed-design analysis of variance. Moderation effects were tested by adding interaction terms (psychological factor×group) in linear regression models of neck-specific disability. Results No significant group differences or group×time interactions were found for psychological outcomes. However, there were significant main effects of time for cognitive-behavioral factors and emotional distress in both groups (all P  < .01), with small to intermediate effect sizes. Psychological factors did not moderate the treatment effects on neck-specific disability. Conclusion The internet-based format (NSEIT), involving fewer clinical visits, did not differ from the more comprehensive physiotherapist-led program (NSE) with regard to psychological outcomes. Improvements in cognitive-behavioral factors and emotional distress occurred over time in both groups. The internet-based format might be suitable regardless of psychological characteristics at baseline. Clinical trial registration www.ClinicalTrials.gov ID: NCT03022812 (December 20, 2016).